Fiqh Aqalliyat: Pergeseran Makna Fiqh dan Usul Fiqh - Ahmad Imam Mawardi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2014)
The basic problems have been faced by minority moslem who live in majority non muslim especially when they have to apply religious interpretation as understood in the majority moslem countries appeared a concept of fiqh al-aqalliyyat (fiqh of minority). It is a kind of islamic teaching that considered as acomodation to contemporary problems faced by minority moslem. Therefore, they can perform their religious teaching eventhought it seems different with the form of islamic law in general. This writing focus on study of form of fiqh alaqalliyyat? What are the principles and the methodological bases of fiqh al-aqalliyyat and what is the relationship between fiqh al-aqalliyyat and maqasid al-syari'ah.